Probing cosmic voids with emission-line galaxies - Yamada, Yuka; Yoshida, Naoki (Frontiers in Astronomy and Space Sciences, 2025)
IntroductionWe aim to provide forecasts for future line intensity mapping (LIM) observations and galaxy redshift surveys, focusing on the physical properties of low-density region of the cosmic web (voids). We study how the measured physical properties depend on the observational methods for void detection and identification.MethodsWe generate mock intensity maps targeting the far-infrared CO(3–2) emission line by assigning the line luminosities to dark matter halos in cosmological simulations. The popular void-finding algorithm VIDE is applied to identify cosmic voids and quantify their properties. We analyze the voids detected in two different observation modes: (1) three-dimensional galaxy redshift surveys and (2) two-dimensional LIM observations corresponding to a single-frequency bin at 173 GHz.ResultsWe find that the measured void size functions and radial density profiles differ depending on the observational method. These features exhibit characteristic signatures that reflect both the underlying cosmology and the nature of the emission-line galaxies.DiscussionLIM-based void detection is a promising avenue for cosmological studies. We discuss the potential of combining LIM and galaxy survey data in a joint analysis to improve constraints on cosmological parameters and to better understand emission-line galaxy populations.